2021
DOI: 10.3390/rs13101929
|View full text |Cite
|
Sign up to set email alerts
|

Ka-Band Radar Cross-Section of Breaking Wind Waves

Abstract: The effective normalized radar cross section (NRCS) of breaking waves, σwb, is empirically derived based on joint synchronized Ka-band radar and video records of the sea surface from a research tower. The σwb is a key parameter that, along with the breaker footprint fraction, Q, defines the contribution of non-polarized backscattering, NP =σwbQ, to the total sea surface NRCS. Combined with the right representation of the regular Bragg and specular backscattering components, the NP component is fundamental to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
2
6
0
Order By: Relevance
“…In particular, they showed that at moderate to high incidence angles, these backscatter spikes represent a non-negligible non-polarized backscatter component associated to quasi specular reflection from breaking facets. Although the contribution of this non-polarized component is shown to be stronger at horizontal polarization than vertical polarization [44], such spikes are also visible in vertical polarization, as shown in [45], and they can also be associated to enhanced roughness of the ocean surface from post wave-breaking events, as described in [46]. Moreover, although the studies of wave breaking effects usually focus on moderate to high wind speed conditions, it was suggested in [38] that the capillary waves observed at Ka-band at low wind speed conditions are generated as parasitic capillary waves from the breaking of short-gravity waves [3], showing a possible breaking contribution at low winds as well.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In particular, they showed that at moderate to high incidence angles, these backscatter spikes represent a non-negligible non-polarized backscatter component associated to quasi specular reflection from breaking facets. Although the contribution of this non-polarized component is shown to be stronger at horizontal polarization than vertical polarization [44], such spikes are also visible in vertical polarization, as shown in [45], and they can also be associated to enhanced roughness of the ocean surface from post wave-breaking events, as described in [46]. Moreover, although the studies of wave breaking effects usually focus on moderate to high wind speed conditions, it was suggested in [38] that the capillary waves observed at Ka-band at low wind speed conditions are generated as parasitic capillary waves from the breaking of short-gravity waves [3], showing a possible breaking contribution at low winds as well.…”
Section: Discussionmentioning
confidence: 90%
“…In this case, the skewness increases from 1.45 to 4.3. Yurovsky et al [44] suggested that the presence of high amplitude spikes, making the distribution strongly skewed in linear space, is likely due to wave breaking events. In particular, they showed that at moderate to high incidence angles, these backscatter spikes represent a non-negligible non-polarized backscatter component associated to quasi specular reflection from breaking facets.…”
Section: Discussionmentioning
confidence: 99%
“…The spectrum can be speculatively partitioned into a low Doppler frequency, f d , "core", associated with orbital motions of surface waves (|V d | < 2 m s −1 ), and high | f d | transient tails, largely associated with radar signal spikes (mostly positive for upwind look geometry). Most of these spikes can also be associated with peaks in the "core" and/or wave breaking events (see more examples in the dedicated study [42]). However, some events occur independent of wave characteristics within the radar footprint.…”
Section: Sea Spray Signaturesmentioning
confidence: 99%
“…This investigation started with a manual inspection of breaker Doppler properties [52]. Following that, a model for the breaker normalized radar cross-section (NRCS) was developed [55] using automated methods for breaker detection. In this paper, the same dataset was used to evaluate breaker Doppler shifts at various observation look geometries using computer vision breaker detection with far richer statistics than that for manual detection.…”
Section: Introductionmentioning
confidence: 99%